Dispersion stabilities and rheological properties of fumed silica suspensions. Issue 5 (4th May 2017) - Kawaguchi, Masami
ABSTRACT: Herein, we have reviewed fumed silica suspensions in dispersing fluids, polymer melts, and polymer solutions, focusing on their dispersion stability and rheological properties as a function of the surface character of fumed silica powders and the silica volume fraction, ϕ. Hydrophilic fumed silica powders are well dispersed at ϕ < 0.01 in polar dispersing fluids or polar polymer melts, and their phase states change from sol to gel with increasing ϕ. Such changes should also be strongly related to the rheological responses of the hydrophilic fumed silica suspensions, which change from Newtonian flow behavior to gel-like elasticity with increasing ϕ. On the other hand, hydrophobic fumed silica powders are stabilized in both polar and nonpolar dispersing fluids, depending on the interactions between the surface hydrophobic moieties and the dispersing fluids, in addition to those between the residual surface silanol groups and dispersing fluid, except for the particle–particle interactions. Moreover, the effects of the adsorption and desorption of polymers, as well as of non-adsorbing polymers on the dispersion stability and rheological behavior of fumed silica suspensions are discussed, by taking account of their optical microscopic observation and SANS curves. GRAPHICAL ABSTRACT: